Advanced research on shallow foundations : proceedings of the 2nd GeoMEast international Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 - The Official International Congress of the Soil-Structure Interaction Group in Egypt (SSIGE) (Cham, Switzerland : Springer, 2019)
This volume deals with the advanced analysis of shallow foundations. Several research studies are considered including soil plasticity, cracking, reaching the soil bearing capacity, creep, etc. Dynamic analyses together with stability analysis are also discussed. It gives wide range of topics dealing with the shallow foundations in different parts of the world. The volume is based on the best contributions to the 2nd GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 - The official international congress of the Soil-Structure Interaction Group in Egypt (SSIGE).
También disponible en formato EPUB